2009
DOI: 10.1371/journal.pone.0005532
|View full text |Cite
|
Sign up to set email alerts
|

Down-Regulation of miR-92 in Human Plasma Is a Novel Marker for Acute Leukemia Patients

Abstract: BackgroundMicroRNAs are a family of 19- to 25-nucleotides noncoding small RNAs that primarily function as gene regulators. Aberrant microRNA expression has been described for several human malignancies, and this new class of small regulatory RNAs has both oncogenic and tumor suppressor functions. Despite this knowledge, there is little information regarding microRNAs in plasma especially because microRNAs in plasma, if exist, were thought to be digested by RNase. Recent studies, however, have revealed that mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
227
1
3

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 274 publications
(245 citation statements)
references
References 32 publications
14
227
1
3
Order By: Relevance
“…[20] Comparison of the ratio of miRNA-92a signal intensity (0.239 ± 0.286) to miR-NA-638 signal intensity by TaqMan qRT-PCR among the plasmas of AML and control samples (0.969 ± 0.490) determined statistical significance difference (p = 0.000) this confirmed downregulation in plasma of miRNA-92a in AML patients This result was in agreement with the study carried out by Tanaka et al [17] on the plasma samples from normal (n = 16) and leukemia (AML, n = 54; ALL, n = 7) by TaqMan qRT-PCR. They reported that miRNA-638 is stably present in human plasmas, and miRNA-92a dramatically decreased in the plasmas of acute leukemia patients.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…[20] Comparison of the ratio of miRNA-92a signal intensity (0.239 ± 0.286) to miR-NA-638 signal intensity by TaqMan qRT-PCR among the plasmas of AML and control samples (0.969 ± 0.490) determined statistical significance difference (p = 0.000) this confirmed downregulation in plasma of miRNA-92a in AML patients This result was in agreement with the study carried out by Tanaka et al [17] on the plasma samples from normal (n = 16) and leukemia (AML, n = 54; ALL, n = 7) by TaqMan qRT-PCR. They reported that miRNA-638 is stably present in human plasmas, and miRNA-92a dramatically decreased in the plasmas of acute leukemia patients.…”
Section: Discussionsupporting
confidence: 89%
“…As miRNA-92a is expressed in the majority of cells at all times, its expression profiles will form a reliable part of diagnosis and detection of disease [17]. The search for noninvasive tools for diagnosis and management of cancer is extremely important for reducing the world wide health burden of cancer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies, however, have shown that there is a strong correlation between elevated microRNA levels, such as miR-92a, in plasma and leukemic cells, suggesting an important role in cellular communication. [44][45][46] In summary, we performed global microRNA expression profiling on plasma samples from 72 patients with de novo myelodysplastic syndromes and 12 healthy individuals (controls). We identified a number of microRNAs that are potential noninvasive biomarkers for diagnosis and prognostication.…”
Section: Discussionmentioning
confidence: 99%
“…Every cancer investigated has a distinct miRNA signature and deregulated levels of miRNAs have been detected in body fl uids of patients, including those with lymphoma, [11] leukemia, [12] colon, [13] breast, [14] prostate, [15] ovarian, [16] pancreatic, [17] gastric, [18] and lung cancer. [19] In the context of brain tumors, recent studies have demonstrated a signifi cant presence of certain miRNAs in CSF samples from patients with central nervous system lymphoma, glioma, and metastatic brain cancers.…”
Section: Introductionmentioning
confidence: 99%